2006
DOI: 10.1002/rra.939
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the effects of dam removal on migratory walleye (Sander vitreus) early life-history stages

Abstract: Many dams in the USA have outlived their intended purpose and an increasing number are being considered for removal. Yet, quantitative studies of the potential physical, biological and ecological responses are needed to assess dam removal decisions. In this paper, the responses of migratory walleye (Sander vitreus) to increased spawning habitat availability as a result of dam removal was studied by comparing scenarios with and without a high-head dam in the Sandusky River (Ohio), a major tributary to Lake Erie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 38 publications
1
26
0
Order By: Relevance
“…Unfortunately, the levels of production necessary to achieve Option 3 are orders of magnitude greater than current production from these production areas. This option may perhaps be an unrealistic target without major investment in mitigating spawning habitat degradation and solving river-to-lake connectivity issues that currently plague Lake Erie's riverine stocks (Mion et al 1998, Cheng et al 2006, Bennion and Manny 2011. If the current and continued cultural demands on these systems preclude sufficient habitat (and hence, stock) rehabilitation in western Lake Erie's spawning tributaries, then management options 4 and 5 may offer the next best targets for optimal production dynamics, as both seem attainable.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Unfortunately, the levels of production necessary to achieve Option 3 are orders of magnitude greater than current production from these production areas. This option may perhaps be an unrealistic target without major investment in mitigating spawning habitat degradation and solving river-to-lake connectivity issues that currently plague Lake Erie's riverine stocks (Mion et al 1998, Cheng et al 2006, Bennion and Manny 2011. If the current and continued cultural demands on these systems preclude sufficient habitat (and hence, stock) rehabilitation in western Lake Erie's spawning tributaries, then management options 4 and 5 may offer the next best targets for optimal production dynamics, as both seem attainable.…”
Section: Discussionmentioning
confidence: 99%
“…Our analysis identified that the quickest path to balancing the larval production portfolio likely starts with improving production from the Sandusky River. Fortunately, managers are in the final stages of a process leading to the removal of the Ballville Dam (USFWS 2014), which should increase access to spawning habitats (Jones et al 2003) and improve larval production (Cheng et al 2006). Removal of this barrier on the most depressed spawning stock could generate immediate dividends to the Lake Erie walleye population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Walleye are native species and top predators in the Lake Erie ecosystem, and are highly valued both ecologically and for sport and commercial fisheries (Locke et al 2005). Historical fisheries data and research (Mion et al 1998;Evans et al 2002;Jones et al 2003;Cheng et al 2006;Gillenwater et al 2006) indicate that, there exists a significant amount of upstream walleye spawning habitat that would be made accessible by removing the dam. But, its removal may also provide access to spawning and nursery habitat for sea lamprey (Petromyzon marinus), an invasive species that negatively impacts the Lake Erie fish community.…”
Section: Introductionmentioning
confidence: 99%
“…The typical representatives include WASP [6], QUAL2E [7], Environmental Fluid Dynamics Code (EFDC) [8], Computational Fluid Dynamics (CFD) [9], and DHI MIKE (Danish Hydraulic Institute) [10]. These models were widely applied to rivers, lakes, estuaries, and water transfer projects with large amount of hydraulic structures (gates, culverts, dams, and bridges) [10][11][12][13]. Although water flow was difficult to be determined when it gets through hydraulic structures, hydraulic regulation was crucial for water resources management and water quality control [14].…”
Section: Introductionmentioning
confidence: 99%